A Search for Dengue 2 Virus Inhibitor from Tripeptides and Hexapeptides - Abd. Rahman, Noorsaadah; K.T, Teoh; Yusof, Rohana (Malaysian Journal of Science, 2005)
Libraries of tripeptides and hexapeptides were screened for inhibitory activity against the dengue protease complex. Libraries of tripeptide showed very weak inhibition towards dengue protease, On the other hand, libraries of hexapeptide, designed based on substrate-based inhibitors, where basic amino acids, such as arginine or lysine at the P1 position incorporated with non-coded amino acids, showed an increase in potency. The library H2L1 was the most promising candidate with 33.0% inhibition (8.0 mg/ml), but library H2L2 (2.0mg/ml) possesses considerably weak inhibition. On theother hand, library H2L3 showed 21.3% inhibition against the protease activity. Overall, libraries of hexapeptide were considered weak in inhibitory effect although they showed better inhibitory activities than the tripeptide libraries. Although the inhibitory activities of these peptide libraries are in the mg/mL range, the combinatorial library synthesized has provided indispensable information towards the design of possible inhibitors.